Effects Of Slag Chemistry And Temperature On Wetting And Penetration Of Refractories By Slags - D. Xie (The Southern African Institute of Mining and Metallurgy, 2004)
An in situ gravimetric technique based on wetting and capillary action principles has been used to investigate the wetting and penetration of synthesized alumina samples and commercial magnesia spinel refractories by CaO-SiO2-Al2O3-Fe2O3slags. Synthetic slags of 40CaO-40SiO2-20Al2O3 (in weight per cent) with 0 to 9 weight per cent Fe2O3were used and the experiments were conducted at temperatures 1370 to 1470ºC under argon. The contact time between the sample and the slag was 30 minutes. The results show that the wetting and penetration are enhanced by the iron oxide addition in the slags. Addition of Fe2O3from 0 to 9 weight per cent resulted in a significant increase in the slag penetration into the magnesia spinel refractory by a factor of about 7 and a moderate increase in the synthesized alumina by about 60 per cent. The addition of Fe2O3enhanced the wetting (??cos?, where ? is the surface tension of the slag and the contact angle between the slag and the refractory) by 5 to 18 per cent. An increase in temperature from 1370ºC to 1470ºC resulted in a significant increase in the penetration of a 6 weight per cent Fe2O3slag in the alumina and magnesia samples by a factor of4 to 5 and a decrease in wetting by approximately 30 per cent. Keywords: refractories, slag penetration, wetting.